(untitled) (De la Crítica, 2020)
As soon as we read the title of Terry Eagleton’s After Theory, we can feel the ironic and subversive language that this author uses to completely dismantle all the pre-established concepts that people have about what he calls high theory. In a precise way, it explains the process of degradation or systematic trivialization, to which intellectual production, and therefore culture, has been subjected. It highlights a complete detachment of the new generations from the old canons, to give way to the everyday or trivial, as the central axis of their productions, a trend that may have as its objective, to respond to the various cultural phenomena that have filled the stage. current social.